2005
DOI: 10.1097/01202412-200507000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal lengthening for planovalgus foot deformity in children with spastic cerebral palsy

Abstract: The purpose of this study was to evaluate the effectiveness of calcaneal lengthening in the treatment of planovalgus foot deformity of children with spastic cerebral palsy. Sixteen children (27 feet) with spastic cerebral palsy underwent calcaneal lengthening along with peroneal tendons. The results were assessed clinically and radiographically. Over an average of 3.2 years of follow-up (2.0-5.0), 20 (74.1%) feet showed a satisfactory clinical result, and 21 (77.8%) feet showed a satisfactory radiographic resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 10 publications
3
28
0
Order By: Relevance
“…In terms of the risk factors, the use of tricortical iliac allograft was found to be superior to patellar allograft, and the risk of radiographic graft failure was found to increase along with age. In terms of the extent of correction, our findings are comparable to those of the previous studied on the topic [1,5,23,25,33,37,38].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In terms of the risk factors, the use of tricortical iliac allograft was found to be superior to patellar allograft, and the risk of radiographic graft failure was found to increase along with age. In terms of the extent of correction, our findings are comparable to those of the previous studied on the topic [1,5,23,25,33,37,38].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, another risk factor for graft failure is age, and our study accordingly showed that the Goldberg score was decreased with increasing age, confirming that older patients may require more time for graft incorporation [11] and have a higher probability of graft failure. Our study measured the degree of correction after calcaneal lengthening by using six radiographic indices, which, in previous studies [1,5,23,25,33,37,38], have been reported to be improved after calcaneal lengthening, and we obtained comparable results (Table 5). In addition, we also investigated the risk factors affecting the extent of correction.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Recently, other corrective surgical procedures have been more commonly used, such as the medial sliding osteotomy of the calcaneus [5,6] and the calcaneal lengthening osteotomy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%